2020
DOI: 10.1371/journal.pone.0237571
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effectiveness of pre-pregnancy care for women with diabetes for improving maternal and perinatal outcomes

Abstract: Background Pre-gestational diabetes mellitus is associated with increased risk of maternal and perinatal adverse outcomes. This systematic review was conducted to evaluate the effectiveness and safety of pre-conception care (PCC) in improving maternal and perinatal outcomes. Methods Databases from MEDLINE, EMBASE, WEB OF SCIENCE, and Cochrane Library were searched, including the CENTRAL register of controlled trials, and CINHAL up until March 2019, without any language restrictions, for any pre-pregnancy care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 84 publications
(194 reference statements)
0
61
1
Order By: Relevance
“…Yu et al performed a meta-analysis of over 40 million pregnancies from 100 studies and found that type 1 diabetes was associated with an increased risk for neonatal hypoglycemia (OR 26.62) [ 207 ]. Wahabi et al found in 880 diabetic pregnancies that pre-pregnancy care may have little or no effect in reducing the risk of neonatal hypoglycemia (RR 0.93) [ 208 ]. The use of real-time continuous glucose monitoring throughout pregnancy was evaluated among women with Type 1 diabetes from 31 hospitals in Canada, England, Scotland, Spain, Italy, Ireland, and the USA [ 209 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
See 3 more Smart Citations
“…Yu et al performed a meta-analysis of over 40 million pregnancies from 100 studies and found that type 1 diabetes was associated with an increased risk for neonatal hypoglycemia (OR 26.62) [ 207 ]. Wahabi et al found in 880 diabetic pregnancies that pre-pregnancy care may have little or no effect in reducing the risk of neonatal hypoglycemia (RR 0.93) [ 208 ]. The use of real-time continuous glucose monitoring throughout pregnancy was evaluated among women with Type 1 diabetes from 31 hospitals in Canada, England, Scotland, Spain, Italy, Ireland, and the USA [ 209 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…In multiple regression analyses, the risk for macrosomia was significantly increased among women with diabetes type 1 (OR 31.3, p < 0.001); multiparity (OR 6.2, p = 0.003): early pregnancy BMI > 30 kg/m 2 (OR 7.2, p = 0.003); gestational weight gain ≥ 8 kg (OR 3.8, p = 0.047) and living alone (OR 18.4, p = 0.02) [ 210 ]. Wahabi et al, found in a meta-analysis that pre-pregnancy care of diabetic women had little or no effect in reducing macrosomia rate (RR 1.06; nine studies, 2787 women) [ 208 ]. The different definitions of GDM (i.e., the Diabetes and Pregnancy Study Group (IADPSG) criteria versus the National Institute for Health and Care Excellence (NICE) in the U.K criteria) affect the rate of macrosomia.…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
See 2 more Smart Citations
“…In no area of obstetrics does the care of the woman before she conceives have as much impact on the outcomes for her and her baby as in diabetes. We have long known that the degree of diabetes control in the periconception period has a huge influence on the risk of miscarriage, congenital anomalies and stillbirth 3‐5 . The guideline highlights the importance of prepregnancy care, with specific advice provided regarding screening for complications of diabetes including renal, retinal, cardiac, autonomic, autoimmune, nutritional and diabetic foot disease.…”
mentioning
confidence: 99%